Biotechnology for Beginner Student - Elly Syafriani; Medina Uli Alba Somala; Nova Triani (Future Science, 2020)
The research aims to produce a textbook for undergraduate students, especially the students of the Agrotechnology Study Program in Agricultural Faculty of UPN “Veteran” Jawa Timur. Since beginner students quite hard to understand the theory and practice of biotechnology in the agricultural field, thus a textbook was needed to help them improved their understanding of all the general and basic knowledge of biotechnology. This research was conducted by collecting any information from some literature due to biotechnology, then write it into a good textbook. Moreover, some of the research results were also reported in it. This textbook was included eight chapters, respectively: 1) definition, history, and the role of biotechnology; 2) genetic materials; 3) gene structure and expression; 4) molecular technique; 5) biotechnology application; 6) molecular marker and biomarker; 7) bioinformatic; and 8) security, management and intellectual property rights of the genetically modified organism. This book was also written completely with some questions as a task for the students in each chapter. As a result, a textbook with the specificity is 205 pages in HVS (A4) size, written in Bahasa, and the title of this book is “Bioteknologi Umum Untuk Mahasiswa Pemula (Teori dan Aplikasi Bioteknologi di Segala Bidang)”. Although this book was aiming at agricultural students, the theory in it was also enriched with biotechnology information in some aspects, such as medical, environmental, and food technology.